Negotiating space, place and power in the postmodern and contemporary encyclopedic novel - Rankin, James M., author; Sorensen, Leif, advisor; Trembath, Paul, committee member; Valerio-Holguin, Fernando, committee member (Colorado State University. Libraries, 2018)
This project examines the shifts of global and cartographical power in the late 20th and early 21st centuries through the lens of the encyclopedic novel. I argue that cartographies of power have become increasingly global, decentralized, and polysystemic during the postwar era. I have selected six novels spanning from 1955 through 2014 to demonstrate how the encyclopedic genre lends itself to the relationships of power with geographical space, as well as the organization of narrative space through the encyclopedic structure. My research points towards the cartelization of both space and power – as global networks emerge, institutional means of control become irreducibly complex and cannot be isolated to traditional centers of authority. The hegemonic apparatus of control that I examine extends from the cultural and aesthetic value systems to the constraints of global mobility and the creation of abject spaces to which subaltern groups are limited. I argue that a rhizomatic approach to mapping, which includes a multicultural and multinational reevaluation of cartographical space, is the only means in which the cartelization of space can be resisted. This project will provide both a genealogy of hegemonic power in the postwar encyclopedic novel and contend with contemporary issues such as global mobility and the systems of violence that disproportionally target subaltern groups.